Theorizing the Role of the Intermediary in Postcolonial (Con)text: Driss Chraïbi's Une enquête au pays - Anjali Prabhu (Studies in 20th & 21st Century Literature, 2003)
The paper is a study of the role of the "intermediary" as exemplified by Inspector Ali in Driss Chraïbi's novel Une enquête au pays. This reading traces his role as the intermediary through a close reading of the construction of this space — between higher levels of administration, implying the more elite strata in Moroccan society, and the Berber peasants who live isolated in the mountains, struggling to subsist. Ali has claims to both of these locations: to the former through education and his position in the police force and to the latter through ancestry and the culture of his childhood. Choice and the variable implications for power that it affords through shifting locations, become key issues in the theoretical significance of this character. While engaging in a careful consideration of the complexity of the intermediary in Chraïbi's text, this study illustrates how an intermediary space can very effectively serve as a point of departure to theorize current issues of interest to postcolonial studies, such as the national space, the position of intellectuals, the question of class and of indigenous modes of existence, and the idea of structure in and beyond the new nation.
Keywords: Driss Chraïbi; novel; Une enquête au pays; close reading; space; constructing space; Moroccan society; Berber peasants; Inspector Ali; intermediary; education; police; ancestry; culture of his childhood; culture; childhood; choice; power; location; shifting locations; point of departure; intermediary space; postcolonial studies; national space; intellectuals; class; indigenous modes of existence; new nation